Effectiveness of Implementing Oxytocy Massage to Stimulate Contractions - Ariani Ariani; Niar Niar; Dian Ayu Lestari; Sumiyati Sumiyati (LPPM STIKes Muhammadiyah Ciamis, 2022)
Childbirth is a process of spontaneous expulsion of the fetus, placenta, and membranes through the birth canal without any complications. In the labor process, the frequency and duration of the hours are very influential. If the frequency and duration of the hys are not good, it will make the labor process take longer and make the mother feel more uncomfortable. The aim of this research is to find out how effective oxytocin massage is in stimulating contractions in the Pekkabata Community Health Center working area. The research method used in this research is an experimental research method. With pre-test and post-test The results of research using the pre-test and post-test showed that the effectiveness of oxytocin massage in stimulating contractions in the Pekkabata Health Center Work Area showed that oxytocin massage was effective in stimulating contractions, with a sign value obtained of 0.016 <0.05. With a significance level of <0.05, this shows that oxytocin massage is effective in stimulating the contractions of mothers giving birth in the Pekkabata Health Center Working Area.